Scouting for strong light–matter coupling signatures in Raman spectra. Issue 31 (29th July 2021) - Takele, Wassie Mersha; Piatkowski, Lukasz; Wackenhut, Frank; Gawinkowski, Sylwester; Meixner, Alfred J.; Waluk, Jacek
Abstract : Changes in the Raman spectra under vibrational strong coupling do not necessarily result from the coupling effect but rather they can be caused by the surface enhancement effect. Abstract : Strong coupling between vibrational transitions and a vacuum field of a cavity mode leads to the formation of vibrational polaritons. These hybrid light–matter states have been widely explored because of their potential to control chemical reactivity. However, the possibility of altering Raman scattering through the formation of vibrational polaritons has been rarely reported. Here, we present the Raman scattering properties of different molecules under vibrational strong coupling conditions. The polariton states are clearly observed in the IR transmission spectra of the coupled system for benzonitrile and methyl salicylate in liquid phase and for polyvinyl acetate in a solid polymer film. However, none of the studied systems exhibits a signature of the polariton states in the Raman spectra. For the solid polymer film, we have used cavities with different layer structures to investigate the influence of vibrational strong coupling on the Raman spectra. The only scenario where alterations of the Raman spectra are observed is for a thin Ag layer being in direct contact with the polymer film. This shows that, even though the system is in the vibrational strong coupling regime, changes in the Raman spectra do not necessarily result from the strong coupling, but are caused by the surface enhancement effects.